Linking drug and food addiction via compulsive appetite. (7th March 2022) - Laque, Amanda; Wagner, Grant E.; Matzeu, Alessandra; De Ness, Genna L.; Kerr, Tony M.; Carroll, Ayla M.; de Guglielmo, Giordano; Nedelescu, Hermina; Buczynski, Matthew W.; Gregus, Ann M.; Jhou, Thomas C.; Zorrilla, Eric P.; et al.
Abstract : Background and Purpose: 'Food addiction' is the subject of intense public and research interest. However, this nosology based on neurobehavioural similarities among obese individuals, patients with eating disorders and those with substance use disorders (drug addiction) remains controversial. We thus sought to determine which aspects of disordered eating are causally linked to preclinical models of drug addiction. We hypothesized that extensive drug histories, known to cause addiction‐like brain changes and drug motivation in rats, would also cause addiction‐like food motivation. Experimental Approach: Rats underwent extensive cocaine, alcohol, caffeine or obesogenic diet histories and were subsequently tested for punishment‐resistant food self‐administration or 'compulsive appetite', as a measure of addiction‐like food motivation. Key Results: Extensive cocaine and alcohol (but not caffeine) histories caused compulsive appetite that persisted long after the last drug exposure. Extensive obesogenic diet histories also caused compulsive appetite, although neither cocaine nor alcohol histories caused excess calorie intake and bodyweight during abstinence. Hence, compulsive appetite and obesity appear to be dissociable, with the former sharing common mechanisms with preclinical drug addiction models. Conclusion and Implications: Compulsive appetite, as seen in subsets of obese individuals and patients with binge‐eating disorder and bulimia nervosa (eating disorders that do not necessarily result in obesity), appears to epitomize 'food addiction'. Because different drug and obesogenic diet histories caused compulsive appetite, overlapping dysregulations in the reward circuits, which control drug and food motivation independently of energy homeostasis, may offer common therapeutic targets for treating addictive behaviours across drug addiction, eating disorders and obesity.